Measurement of Natural Radioactivity in Porcelain Stoneware Tiles - B. Rajamannan, G. Viruthagiri, R. Gobi (Recent Research in Science and Technology, 2009)
This paper presents the results of the measurement of natural radio activity present in the Porcelain stoneware tiles samples collected from the ceramic firms of Government Ceramic institute, Virudhachalam.Ã‚Â Natural radioactivity in the porcelain stoneware tiles samples in mainly due to 226Ra, 232Th and 40K and their daughter products.Ã‚Â In this study, these measurements have been estimated in Gamma-ray spectrometry and their levels for six samples are compared and also the Radium equivalent concentration (Raeq) is calculated. The gamma index is calculated and compared well with the reported values.